Ocena wpływu wymiaru przestrzeni zmiennych na jakość predykcji wybranych nieparametrycznych modeli regresji - Trzęsiok, Joanna (The Impact of the Number of Variables on the Prediction Accuracy in Selected Nonparametric Regression Models, 2009)
The paper presents the procedure for variable selection for regression models built with the use of two nonparametric methods: POLYMARS and projection pursuit regression. The results obtained on the benchmark data sets show that using the procedure for the reduction of the number of predictors yields models with smaller mean squared errors than models built on the complete set of the input variables. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 141-148